Animasi Youtube dalam Pembelajaran Menyimak Bahasa Jerman - Trie Ayu Aprianti; Jufri Jufri; Nurming Saleh (Phonologie : Journal of Language and Literature, 2022)
Abstract. This aim of this research was to obtain data and information on the effectiveness  of  Youtube  animation on listening German skill for X IPS SMA Kartika  XX-1  Makassar.  The type  of this research is a quasi-experimental (nonequivalent control group design). The population of this research is the students of class X IPS SMA Kartika XX-1 Makassar with 47 students. The sample of this research is the students of class X IPS 1 with 24 students as the experimental class and students of class X IPS 2 with 23 students as the control class and selected by total sampling. The results of data analysis obtained through t-count = 5.562 > t- table = 2.014 and the value of sig. (2- tailed) = 0.000 < 0.05 at a significance level of 0,05. This results of this study indicate that the use of Youtube animation was effective in German listening skill of class X IPS students of SMA Kartika XX-1 Makassar.Keywords: Youtube Animation, Listening Skills, German.